1992
DOI: 10.1159/000118800
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-Pituitary-Adrenal Axis Function in Chronic Schizophrenia: Association with Clinical Features

Abstract: The function of the hypothalamic-pituitary-adrenal axis (HPA-axis) and its association with clinical features in chronic schizophrenia were investigated. Twenty of 33 chronic schizophrenics exhibited an abnormal diurnal variation of the saliva cortisol level. The patients with abnormal diurnal variation gave higher scores for some negative symptoms than those with normal diurnal variation. On the dexamethasone suppression test (DST) of saliva samples, 13 of 34 chronic schizophrenics were abnormal. The patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
37
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 15 publications
7
37
0
Order By: Relevance
“…Our study showed that plasma cortisol levels were significantly elevated in the group of patients with schizophrenia compared with controls, which is in agreement with the results of most of the studies [2][3][4][5][6][7][8][9]. However there arestudies reporting no significant differences between the schizophrenic patients and healthy controls in terms of cortisol levels [10,29], as well as lower cortisol levels in patients with schizophrenia [11].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our study showed that plasma cortisol levels were significantly elevated in the group of patients with schizophrenia compared with controls, which is in agreement with the results of most of the studies [2][3][4][5][6][7][8][9]. However there arestudies reporting no significant differences between the schizophrenic patients and healthy controls in terms of cortisol levels [10,29], as well as lower cortisol levels in patients with schizophrenia [11].…”
Section: Discussionsupporting
confidence: 92%
“…Authors of some previous studies found positive correlation between cortisol levelsand negative symptoms [7,17,26,30]. In contrast, some other studies found a correlation between serum cortisol and positive symptoms [2,5,25,31]. It has been suggested that the relation between cortisol levels and symptom severityis due to the augmenting effects of cortisol on dopamine activity [27].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations